2019
DOI: 10.1016/j.toxrep.2019.01.004
|View full text |Cite|
|
Sign up to set email alerts
|

Acute glufosinate-based herbicide treatment in rats leads to increased ocular interleukin-1β and c-Fos protein levels, as well as intraocular pressure

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In contrast, glufosinate exposure to eyes increased intralocular pressure in mice suggesting that the herbicide could damage the optic nerves when improperly handled. 39 The sub-chronic feeding studies of glufosinate were carried out over 3 months at various concentrations using rats (up to 4000 mg kg −1 diet), mice (up to 1280 mg kg −1 diet), and dogs (up to 256 mg kg −1 diet). 40 The 'no observed adverse effect levels' were 2-4 mg kg −1 d −1 for dogs, 4.1 for rats and 17 for mice.…”
Section: Glufosinate Toxicologymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, glufosinate exposure to eyes increased intralocular pressure in mice suggesting that the herbicide could damage the optic nerves when improperly handled. 39 The sub-chronic feeding studies of glufosinate were carried out over 3 months at various concentrations using rats (up to 4000 mg kg −1 diet), mice (up to 1280 mg kg −1 diet), and dogs (up to 256 mg kg −1 diet). 40 The 'no observed adverse effect levels' were 2-4 mg kg −1 d −1 for dogs, 4.1 for rats and 17 for mice.…”
Section: Glufosinate Toxicologymentioning
confidence: 99%
“…In the same study, glufosinate was non‐sensitizing to dermal or eye exposure, but was moderately irritating to the eyes due to some of the adjuvants in the formulation. In contrast, glufosinate exposure to eyes increased intralocular pressure in mice suggesting that the herbicide could damage the optic nerves when improperly handled 39 . The sub‐chronic feeding studies of glufosinate were carried out over 3 months at various concentrations using rats (up to 4000 mg kg −1 diet), mice (up to 1280 mg kg −1 diet), and dogs (up to 256 mg kg −1 diet) 40 .…”
Section: Glufosinate Toxicologymentioning
confidence: 99%
“…Glutamate is known as an excitatory neurotransmitter and plays a crucial role in the plasticity of the central nervous system (CNS) (1,2). When the glutamate concentration is abnormally high, it functions as a neurotoxin and leads to cell death (3). Excessive glutamate levels damage cellulr components, including the mitochondria, and promote the generation of reactive oxygen species (ROS) and induce cell death (4).…”
Section: Introductionmentioning
confidence: 99%
“…The use of pesticides in agriculture, industry, and domestic applications results in increased exposure to these chemicals (Sevim et al, 2019). As a result of acute exposure, it has been observed that human health is highly affected.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of acute exposure, it has been observed that human health is highly affected. Glufosinate is one of the most widely used herbicide-based pesticides worldwide (Comakli et al, 2019). Glufosinate, which is one of the main pollutants of rivers and various water resources, has a toxic effect not only on organisms, but also on food, feed and ecosystems (Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%